Cellular Chaperones As Therapeutic Targets in ALS to Restore Protein Homeostasis and Improve Cellular Function - Kalmar, Bernadett; Greensmith, Linda (Frontiers in Molecular Neuroscience, 2017)
Heat shock proteins (Hsps) are ubiquitously expressed chaperone proteins that enable cells to cope with environmental stresses that cause misfolding and denaturation of proteins. With ageing this protein quality control machinery becomes less effective, reducing the ability of cells to cope with damaging environmental stresses and disease-causing mutations. In neurodegenerative disorders such as Amyotrophic Lateral Sclerosis (ALS), such mutations are known to result in protein misfolding, which in turn results in the formation of intracellular aggregates cellular dysfunction and eventual neuronal death. The exact cellular pathology of ALS and other neurodegenerative diseases has been elusive and thus, hindering the development of effective therapies. However, a common scheme has emerged across these “protein misfolding” disorders, in that the mechanism of disease involves one or more aspects of proteostasis; from DNA transcription, RNA translation, to protein folding, transport and degradation via proteosomal and autophagic pathways. Interestingly, members of the heat shock protein (Hsp) family are involved in each of these steps facilitating normal protein folding, regulating the rate of protein synthesis and degradation. In this short review we summarize the evidence that suggests that ALS is a disease of protein dyshomeostasis in which Hsps may play a key role. Overwhelming evidence now indicates that enabling protein homeostasis to cope with disease-causing mutations might be a successful therapeutic strategy in ALS, as well as other neurodegenerative diseases. Novel small molecule co-inducers of Hsps appear to be able to achieve this aim. Arimoclomol, a hydroxylamine derivative, has shown promising results in cellular and animal models of ALS, as well as other protein misfolding diseases such as Inclusion Body Myositis (IBM). Initial clinical investigations of Arimoclomol have shown promising results. Therefore, it is possible that the long series of unsuccessful clinical trials for ALS may soon be reversed, as optimal targeting of proteostasis in ALS may now be possible, and may deliver clinical benefit to patients.